Peningkatan Karakter Mahasiswa Program Studi PGSD pada Mata Kuliah Pengembangan Pembelajaran IPA SD di Universitas Muhammadiyah Sidoarjo: Character Development of PGSD Study Program Students in Elementary Science Learning Development Courses at Muhammadiyah University of Sidoarjo - Setiyawati, Enik; Rocmah, Luluk Iffatur (Universitas Muhammadiyah Sidoarjo, 2017)
PGSD student's character can be seen from various aspects of the attitude that must be owned by an educator, especially educators in primary school. Some of these aspects are honesty, cooperation, discipline, responsibility, and independence. Aspects of honesty student still low category, the aspect of cooperation, discipline, responsibility, and independence are being categorized. The purpose of this research is to describe the increase in student character study program PGSD On Learning Course Development IPA SD At the University of Muhammadiyah Sidoarjo. In conducting the study, researchers used a classroom action research (Classroom Action Research). Based on the results of the study in the first cycle and the second cycle, it can be seen that there is a rise in the value of the character of students in primary school teaching courses Learning Development IPA SD from the first cycle to the second cycle. Value of character in the first cycle of 71.4, while the value of the character in the second cycle of 98.5. This shows that there is an increase of 27.1 of all indicators of character shown by students of primary school teaching course on development of Elementary Science Lesson.